Human lower limb muscle cross sectional area scales with positive allometry reflecting bipedal evolutionary history - Warrener, Anna (Frontiers in Earth Science, 2024)
Muscle cross-sectional area is an important variable for understanding force generating potential and locomotor adaptation. Geometric scaling predicts area scales proportionally to body mass 2/3 . Previous research has quantified scaling relationships between hindlimb musculature and mass in apes, but these relationships have not been clearly established in humans. Scaling in the human lower-limb is likely influenced by bipedalism and dimorphism in lean and total body mass between the sexes. To investigate these relationships, cross-sectional area in 20 muscles of the lower-limb were obtained through MRI in twenty-eight (14 female, 14 male) participants and measured in Analyze 14.0. Log transformed muscle cross-sectional areas were grouped by function (gluteals, knee extensors, hamstrings, biarticulate knee/hip flexors, plantarflexors), and least-squares regressions were calculated for each group against log-body mass. All muscle groups were significantly (p < 0.001) correlated with mass (0.56 < r 2 < 0.70) and, except for the gluteals, all groups scaled with positive allometry with slopes outside the 95% CI reported in the literature for apes. Correlations and slopes were lower for females (0.05 < r 2 < 0.62; 0.40 < b < 1.02), than males (0.56 < r 2 < 0.79: 0. 7< b < 1.9) in all muscle groups, but there were no statistically significant differences in slope except for the tensor fasciae latae and the hamstrings. However, including sex as a predictor in multiple regression analysis increased the explained variance in cross-sectional area by 1-18% across functional muscle groups. These results suggest human lower-limb muscle scaling has responded to force production requirements of bipedalism, but differences in lean and total mass do not clearly impact allometric equations in males and females.